Optimasi Performa Mesin Diesel Matsumoto MDX-178F melalui Modifikasi Intake dan Exhaust - Dibyo Setiawan; Rizal Jatnika; Derry Murtadho Muthohhary; Ilham Azmy; Toni Okviyanto; Cahyo Wibowo (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2026)
The current condition of the Matsumoto MDX-178F diesel engine for the Energy Efficient Car Competition (KMHE) is not at its maximum performance, the efficiency and torque it produces have decreased from the initial engine specifications. The purpose of this activity is to recondition and modify the air intake and exhaust system on the Matsumoto MDX-178F diesel engine to optimize engine performance, increase combustion efficiency, and reduce exhaust emissions. The reconditioning method begins with an evaluation of the air intake and exhaust system which includes components such as air ducts, filters, exhaust ducts, head parts, pistons, cylinders, injectors and other parts. Repairs or replacements are carried out on components that are damaged or require readjustment. The modification process is carried out by porting and polishing the intake and exhaust lines. The increase in air flow is measured using a flow bench, the increase in power is measured using a dynotest, the reduction in exhaust emissions is measured using an exhaust gas analyzer. This study provides a scientific contribution through the integrated application of reconditioning and geometric optimization of intake–exhaust channels based on porting and polishing in a single-cylinder diesel engine within the context of energy-efficient vehicles, an area that remains limited in previous research. The results of this reconditioning and modification can show a significant increase in engine performance, including increased power and combustion efficiency. so that the engine becomes more environmentally friendly. The conclusion shows that the reconditioning and modification of the intake and exhaust systems of the Matsumoto MDX-170F diesel engine not only improves engine performance, but also improves fuel economy and reduces environmental impact.